Enhancing Germination and Early Growth of Curly Lettuce Using Fermented Liquid Extract of Padina australis Hauck - Liew Wei Yi; Sarayu Krishnamoorthy; Yumni Haziqah Mohammad; Ummul Hasanah Hassan; Khairul Mardhiah Abidin; Faizah Metali (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Fermented seaweed liquid extract serves as an affordable and eco-friendly nutrient supplement, biostimulant, or biofertilizer, effectively promoting crop growth and supporting sustainable agricultural practices. This study evaluates the effects of the fermented liquid extract of Padina australis (FLEP) at various concentrations (0, 2, 5, 10, 20, and 100%) on lettuce germination and early growth. Germination parameters were assessed over 14 days under controlled conditions, followed by consecutive greenhouse experiments that examined the impact of foliar FLEP spray on two-week-old seedlings over 21 days, measuring early growth parameters and foliar nutrient concentrations. All data were statistically analyzed using a one-way analysis of variance at a 5% significance level. Results revealed that the FLEP significantly improved the seedling vigor index and length at concentrations ranging from 2 to 20%. The relative growth rate (RGR) for height exhibited significant increases at the 2% and 5% FLEP concentrations, while RGR for leaves, shoot dry biomass, and leaf area demonstrated significant improvements at FLEP concentrations of 2 to 20%. Foliar P content, and not foliar N, was significantly affected by the FLEP treatments, with P levels typically increasing with higher FLEP concentrations. These findings suggest that applying FLEP, particularly at low concentrations (2% and 5%) as a foliar spray significantly enhances lettuce germination and growth. Furthermore, this study highlights the potential of the FLEP as a novel foliar biofertilizer.